Party cohesion in presidential races: Applying social network theory to the preprimary multiple donor networks of 2004 and 2008. (July 2015) - Yang, Song; Limbocker, Scott; Dowdle, Andrew; Stewart, Patrick A; Sebold, Karen
Scholars have long been examining the presidential nomination process in the United States. In addition to studies considering the selection mechanism itself, there has been a movement towards analysing the contest even before voting begins. Campaign finance allows for a reliable and valid means to examine the year prior to the nomination with data that are not just vast in quantity but also consistent across time. Donors who gave to multiple campaigns represent a particularly important subset of elite participants in elections whose behaviour shed light on phenomena of parties functioning as a network. We find only rare instances of multiple donors giving across party and that Democratic contributors function as a far more cohesive unit. Also, without any supervising entity, the candidate that amasses the most shared donors goes on to win the nomination in the 2004 and 2008 presidential elections.